An Electrochemical Sensor for Detection of Neuroblastoma Markers: Complexation Studies as a Tool for the Selection of a Suitable Receptor for Electrode Coating. Issue 8 (9th August 2022) - Salvadori, Karolína; Páleš, Jakub Marián; Shishkanova, Tatiana V.; Trchová, Miroslava; Fajgar, Radek; Matějka, Pavel; Cuřínová, Petra
Abstract: Homovanillate (HVA) and vanilmandelate (VMA) are recognized markers of diseases, including neuroblastoma. However, their detection in urine represents a challenging task due to the complexity of the matrix. Here, a design, synthesis and thorough investigation of polymerizable urea‐based receptors interacting with HVA and VMA are reported. The selection of receptor with the best anion recognition properties for electrode coating is based on 1 H‐NMR and UV‐Vis complexation studies. The sensor is prepared by electropolymerization with progress monitoring by cyclic voltammetry. The deposited layer is characterized by IR and scanning electron microscopy. The obtained sensor shows an electrochemical impedance spectroscopy response to VMA with linear range 9.9×10 −6 to 1.2×10 −3 M and LOD of 3.4×10 −6 M. The sensor selectivity was demonstrated by the determination of VMA level in the presence of 16 μM HVA and in artificial urine with and without phosphates, with standard deviations of 0.11, 0.17 and 0.09, respectively. Abstract : The determination of catecholamine metabolites levels in urine represents a quick screening tool for early detection of juvenile neuroblastoma. This work reports an electrochemical sensor, prepared by electropolymerization of receptors to the surface of platinum electrode. The selectivity of the sensing layer is ensured by the specific interaction between the targeted analytes and receptor sites.